Využití metod 3D tisku při návrhu konstrukcí leteckých nadzemních návěstidel - Búliková, Tereza (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Práce se zabývá využitím 3D metod při návrhu výroby nosné části leteckého nadzemního návěstidla s přihlédnutím ke všem požadavkům uvedených v leteckých předpisech a konstrukčních manuálech. Výběr 3D metody a příslušného materiálu bude oproti současné situaci cílit na alternativní variantu výroby takového prvku.

This thesis deals with the usage for 3D methods in the design of a structural element of elevated runway edge light taking into account all the requirement specified in aviation regulations and desing manuals. The choice of 3D method and the relevant material is the goal to find an alternative variant of production unlike the production in current situation.
Application of the 3D printing methods in the design of aerial elevated light fixtures and supporting structures
Keywords: Postranní nadzemní návěstidlo; Aerodrome desing manual - křehkost; lámací mechanismus; lámací spojka; 3D technologie; 3D materiály; slicování; Elevated runway edge light; Aerodrome desing manual - frangibility; break-away mechanism; breakable coupling; 3D technologies; 3D materials; slicing